2003
DOI: 10.1038/sj.onc.1206077
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 is an inhibitor of the Fas pathway as identified by Achilles' Heel Method, a new function-based approach to gene identification in human cells

Abstract: Here we describe the Achilles' Heel Method (AHM), a new function-based approach for identification of inhibitors of signaling pathways, optimized for human cells. The principle of AHM is the identification of 'sensitizing' cDNAs based on their decreased abundance following selection. As a proof of principle, we have employed AHM for the identification of Fas/CD95/APO-1 pathway inhibitors. HeLa cells were transfected with an antisense cDNA expression library in an episomal vector followed by selection with a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 43 publications
(42 reference statements)
0
49
0
Order By: Relevance
“…Nrf2 exhibits a proclivity for dimerization with the transcription factors c-Jun, Jun B, Jun D, ATF3, ATF4, and small Mafs (3)(4)(5)(6). Heterodimeric binding to antioxidant response elements (ARE: 5′-(A/G)TGA (C/G) NNNGC-3′) (7,8) located in the proximal promoter of target genes initiates Nrf2-directed expression of more than 200 gene products, such as those involved in phase II detoxication, antioxidant gene expression, apoptosis, cell growth, and proteasomal activity (9) (2,10). Nrf2 regulates both the constitutive and inducible expression of this stress response network and may be considered a node for the integration of stress signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 exhibits a proclivity for dimerization with the transcription factors c-Jun, Jun B, Jun D, ATF3, ATF4, and small Mafs (3)(4)(5)(6). Heterodimeric binding to antioxidant response elements (ARE: 5′-(A/G)TGA (C/G) NNNGC-3′) (7,8) located in the proximal promoter of target genes initiates Nrf2-directed expression of more than 200 gene products, such as those involved in phase II detoxication, antioxidant gene expression, apoptosis, cell growth, and proteasomal activity (9) (2,10). Nrf2 regulates both the constitutive and inducible expression of this stress response network and may be considered a node for the integration of stress signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The reports strongly indicated that Nrf2 activity may influence the sensitivity of death signaling, but the relationship between Nrf2 and apoptotic signaling was not clearly characterized. Recently, Kotlo et al (2003) demonstrated that inactivation of Nrf2 by antisense or by using a membranepermeable dominant-negative polypeptide sensitized cells while, conversely, overexpression of Nrf2 protected cells from Fas-induced apoptosis. In addition, they demonstrated that N-acetyl-l-cysteine (NAC), a precursor to GSH, protected cells from Fas-mediated killing in HeLa cells.…”
mentioning
confidence: 99%
“…Consequently, Nrf2-induced ARE activation coordinates the expression of many genes involved in combating oxidative stress and toxicity in a wide variety of tissues and cell types (35)(36)(37)(38)(39)(40)(41). In addition to protecting against chemical insults, carcinogenesis, and aging (41)(42)(43)(44), Nrf2 has been shown to directly inhibit Fas-mediated apoptosis, a substrate for caspase-3-like proteases and an effector of PK-like ER kinase-mediated cell survival (45)(46)(47)(48).…”
mentioning
confidence: 99%